The Effect of Training, Mentoring, and Capital Assistance on the Income of SME Entrepreneurs in Mamuju Sub-District, Mamuju District, Indonesia - Ridwan, Muh.; Herman, H.; Mappigau, Ernawaty (Manunggal Halim Jaya, 2024)
This study aims to test and analyze the impact of training, mentoring, and capital assistance on the income of UMKM (Micro, Small, and Medium Enterprises) actors in Mamuju District, Mamuju Regency. The data used in this study consists of both qualitative and quantitative data sourced from secondary and primary data. Multiple linear regression analysis is employed to analyze the data. The study's results indicate the following: (1) The Training variable partially positively affects the income of UMKM actors in Mamuju District, Mamuju Regency. (2) The Mentoring variable also has a partial positive effect on the income of UMKM actors in Mamuju District, Mamuju Regency. (3) The Capital Assistance variable partially positively affects the income of UMKM actors in Mamuju District, Mamuju Regency. Finally, (4) The Training, Mentoring, and Capital Assistance variables, when considered simultaneously, significantly affect the income of UMKM actors in Mamuju District, Mamuju Regency.